Jurisdiction Regarding The Objective Rights Of Buyer Asset-Backed Securities In Secondary Housing Financing - Junitin Sinar Humombang N (Institute Of computer Science (IOCS), 2021)
Secondary housing financing is a facility that makes it easier for banks to liquidate their less liquid financial assets in the form of receivables arising from the distribution of Home Ownership Loans (KPR). This needs to be done to avoid mismatch funding. The title of this research is “Juridic Review On The Objective Rights Of The Buyer Of Asset-Backed Securities In Secondary Housing Financing”. The research was conducted to find out what are the material rights of asset-backed securities holders in housing secondary financing, how is the transition mechanism, what is the legal protection for asset-backed securities holders and whether national laws need to be adjusted to the concept of secondary housing finance. As for this writing, it can be concluded that the material rights attached to asset-backed securities in housing secondary financing owned by the buyer/holder of asset-backed securities include the right to receive payments, the right to transfer ownership of the asset-backed securities, the right to charge or make asset-backed securities as collateral for the settlement of debts from asset-backed securities holders, the right to obtain settlement of receivables due to mortgage rights on houses and land used as collateral for mortgages (KPR), the right to obtain disclosure of material facts, the right to obtain interest (for asset-backed securities that are debt), the right to Get Settlement of Receivables from the Issuer's Assets. Apart from that, it can also be concluded that the mechanism for the transfer of rights to the issuance of asset-backed securities in secondary housing financing generally consists of 4 phases, namely, among others, the emergence of receivables (receivables) through the distribution of housing loans, sales of receivables by original creditors to third parties. issuer, transfer of material rights in the form of receivables to investors with the issuance of asset-backed securities, transfer of asset-backed securities between one investor to another. Regarding legal protection for buyers/holders of asset-backed securities, it can be concluded that legal protection for buyers/holders of asset-backed securities in secondary mortgage financing is broadly divided into two, namely preventive legal protection and repressive legal protection. Preventive legal protection for holders of asset-backed securities in secondary housing financing lies in implementing the disclosure principle in capital market law, especially in secondary housing financing. Meanwhile, repressive legal protection for asset-backed securities holders consists of 2, namely, legal protection against unlawful acts and legal protection against default acts, both of which must go through a judicial process and cannot be carried out individually but can only be implemented by investment managers in If the asset-backed securities are in the form of securities (equity security)/unit of participation, while if the securities are debt security, the legal action must be carried out through a trustee.